Enkätundersökning om skogsbruksplaner i Kalmar län - Rosberg, Henrik (2017)
This survey has been made in Kalmar county concerning forest management plans. The survey has been done to see what private forest owners think of their forest management plans and what they think about forest management plans in general. The survey was conducted in cooperation with LRF Konsult. The questionnaire has been sent out in the form of a letter. The first survey mailing was done in the middle of February and a reminder was sent out after three weeks. 330 questionnaires was sent out and responses was received from 56 percent. The average size of private owned forest properties in this surveys larger than the average in Sweden. The average property for the respondents is more than 100 hectares. The goal of forest ownership varied very much. Income of timber was valued highest while hunting and wildlife management was ranked lowest by the forest owners. Overall, forest owners were satisfied with their forest management plans. 85 percent responded that they were satisfied with their forest management plans. It was 82 percent of forest owners who had a current forest management plan. For owners who did not have a current forest management plan was the most common reason that they had ordered a new but have not received it yet. It was 89 percent of forest owners who thought it was good to have a conversation with the planner before the design is carried out. Forest owners consider the most interesting/important thing in a forest management plan is the manage proposals. In second place the compartment descriptions and third place of most interesting/important in a forestry plan for private forest owners is timber volume. Forest owners were generally satisfied with the accuracy of the volume data by compartment. It was only 7 percent of the forest owners who were not satisfied with the accuracy of the volume data. 61 percent responded that they would not be willing to pay more for a forest management plan if it had greater precision in volume. Only 12 percent of the forest owners were willing to pay more for better precision of the volume data. The remaining 27 percent said they did not know. There was a great interest for more individually adapted forestry plans. It was as much as 41 percent who responded that there was an interest in such management plans. 28 percent of the forest owners were not interested in more individually adapted management plans. 31 percent of the forest owners answered I don’t know.